Computer adaptive testing to assess impairing behavioral health problems in emergency department patients with somatic complaints - Lauren M. O'Reilly; Azhar I. Dalal BS; Serena Maag MS; Matthew T. Perry BS; Alex Card DO; Max B. Bohrer BS; Jackson Hamersly BS; Setarah Mohammad Nader MD; Kelli Peterson RN; David G. Beiser; Robert D. Gibbons; Brian M. D'Onofrio; et al. (Journal of the American College of Emergency Physicians Open)
Abstract Objectives To assess: (1) the prevalence of mental health and substance use in patients presenting to the emergency department (ED) through use of a computer adaptive test (CAT‐MH), (2) the correlation among CAT‐MH scores and self‐ and clinician‐reported assessments, and (3) the association between CAT‐MH scores and ED utilization in the year prior and 30 days after enrollment. Methods This was a single‐center observational study of adult patients presenting to the ED for somatic complaints (97%) from May 2019 to March 2020. The main outcomes were computer‐adaptive‐assessed domains of suicidality, depression, anxiety, post‐traumatic stress disorder (PTSD), and substance use. We conducted Pearson correlations and logistic regression for objectives 2 and 3, respectively. Results From a sample of 794 patients, the proportion of those at moderate/severe risk was: 24.1% (suicidality), 8.3% (depression), 16.5% (anxiety), 12.3% (PTSD), and 20.4% (substance use). CAT‐MH domains were highly correlated with self‐report assessments (r = 0.49–0.79). Individuals who had 2 or more ED visits in the prior year had 62% increased odds of being in the intermediate‐high suicide risk category (odds ratio [OR], 1.62; 95% confidence interval [CI], 1.07–2.44) compared to those with zero prior ED visits. Individuals who scored in the intermediate‐high‐suicide risk group had 63% greater odds of an ED visit within 30 days after enrollment compared to those who scored as low risk (OR, 1.63; 95% CI, 1.09, 2.44). Conclusion The CAT‐MH documented that a considerable proportion of ED patients presenting for somatic problems had mental health conditions, even if mild. Mental health problems were also associated with ED utilization.